Development of Kampung Komet Ectourism with Application of Smart Tourism 4.0 in Punjul Village, Kediri District - Putri, Sefhia Alika; PHP2D HMJ-BK UNESA (Talenta Publisher, 2023)
Punjul village is one of the villages in the plosoklaten sub-district which is included as the outermost village of the sub-district. This village has a lot of natural potential because of its location close to Mount Kelud, the natural potential includes products from agriculture, plantations and animal husbandry. Starting from food to complete side dishes in Punjul Village. The results of his farm such as cows, goats, and chickens. While the highest yields from agriculture are rice and corn. Interestingly, agriculture in Punjul Village is not only for planting plants, but there is also a fish farm. One of the potential villages in Kediri Regency is famous for its ornamental fish such as tilapia, koi, and the most common is comet fish. In order to be better known by the people of Kediri and raise the economy of the residents, this village has a goal to establish a tourist village, the potential that will be appointed to be used as a branding for this village is